1991
DOI: 10.1111/j.1476-5381.1991.tb12472.x
|View full text |Cite
|
Sign up to set email alerts
|

Amantadine and sparteine inhibit ATP‐regulated K‐currents in the insulin‐secreting β‐cell line, HIT‐T15

Abstract: 1 The effects of pharmacological agents that potentiate insulin release were studied on ATP-regulated K-currents (K-ATP currents) in the insulin-secreting fl-cell line HIT-T15 by use of patch-clamp methods.2 The tricyclic drug, 1-adamantanamine (amantadine), reversibly inhibited both whole-cell currents (with a Ki of 120pUM) and single channel currents in inside-out patches. This effect was principally due to an increase in a long closed state which reduced the channel open probability. The related compound, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

1993
1993
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 27 publications
0
10
0
1
Order By: Relevance
“…Relationship between Log IC 50 of K ATP and logP values for compounds that block beta‐cell K ATP channel activity. Key: Am, amantadine; BDM , 2,3‐butanedione monoxime; Cib, cibenzoline; Cic, ciclazindol; Clo, clonidine; Dis, disopyramide; Eng, englitazone; Gat, gatifloxacin; gen, genistein; Glp, glipizide; Gly, glibenclamide; Glc, gliclazide; Hal, haloperidol; Hex, 2‐n‐hexyl‐4‐benzoxazine; Mef, mefloquine; Meg, meglitinide; Peb, pentobarbitone; Phb, phenobarbitone; Phe, phentolamine; Qun, quinine; Rep, repaglinide; Rog, rosiglitazone; Seb, secobarbitone; Sim, simvastatin; Spa, sparteine; Tem, temafloxacin; Ter, terfenadine; Thp, thiopentone; Tb, tolbutamide; Trg, troglitazone; TX , Triton X‐100 . Log IC 50 values are from respective references.…”
Section: Methodsmentioning
confidence: 99%
“…Relationship between Log IC 50 of K ATP and logP values for compounds that block beta‐cell K ATP channel activity. Key: Am, amantadine; BDM , 2,3‐butanedione monoxime; Cib, cibenzoline; Cic, ciclazindol; Clo, clonidine; Dis, disopyramide; Eng, englitazone; Gat, gatifloxacin; gen, genistein; Glp, glipizide; Gly, glibenclamide; Glc, gliclazide; Hal, haloperidol; Hex, 2‐n‐hexyl‐4‐benzoxazine; Mef, mefloquine; Meg, meglitinide; Peb, pentobarbitone; Phb, phenobarbitone; Phe, phentolamine; Qun, quinine; Rep, repaglinide; Rog, rosiglitazone; Seb, secobarbitone; Sim, simvastatin; Spa, sparteine; Tem, temafloxacin; Ter, terfenadine; Thp, thiopentone; Tb, tolbutamide; Trg, troglitazone; TX , Triton X‐100 . Log IC 50 values are from respective references.…”
Section: Methodsmentioning
confidence: 99%
“…Sulphonylureas, which are used to increase the ability of the pancreatic P-cell to release insulin in response to glucose stimulation, are known to inhibit specifically the KATP channel (Sturgess et al, 1985;Trube et al, 1986). It has also been reported that the KATP channel is blocked by quinidine in cardiac myocytes (Undrovinas et al, 1990) and by sparteine, an antiarrhythmic agent with oxytocic action, in the insulin-secreting ,-cell line, HIT T15 (Ashcroft et al, 1991). Similarly, it is likely that the KATP channel in pancreatic P-cells may be involved in antiarrhythmic agent-induced hypoglycaemia.…”
Section: Introduction Methodsmentioning
confidence: 99%
“…But at concentrations of two to three orders in magnitude higher than those required to block M2 it also inhibits K + channels (e.g. [22]). Hence the inhibitory effect of amantadine on the PBCV‐1 evoked rise in bisoxonol fluorescence is best understood in the context of a low affinity block of K + channels.…”
Section: Similarities Between Inhibition Of Kcv and Pbcv‐1 Induced Mementioning
confidence: 99%
“…One hour incubation reduces infectivity ∼50% [23]. To test the hypothesis that the Kcv channel is associated with the viral membrane, we incubated PBCV‐1 for 5 days in chloroform or toluene (for details see [21]). Chorella NC64A cells were then incubated with untreated or solvent treated viruses.…”
Section: Pbcv‐1 Induced Membrane Depolarization Requires Intact Viralmentioning
confidence: 99%